Managing employees with dementia: a systematic review. (27th November 2018) - Thomson, L; Stanyon, M; Dening, T; Heron, R; Griffiths, A
Abstract: Background: The experience of developing dementia while in employment has been explored from the point of view of the employee, but less is known about the perspectives, experiences and needs of employers. Aims: To review systematically literature about the management of employees who develop dementia whilst in employment. Methods: Databases searched included MEDLINE, EMBASE, PsycINFO, CINAHL, BNI, ABI Inform, ISI Web of Science, Open Grey and dementia journals database; 44 documents were identified for inclusion in the review: 22 journal papers, one PhD thesis and 21 articles, reports and webpages from the grey literature. As all documents were qualitative in nature a thematic synthesis of their content was undertaken. Results: Three main themes and ten sub-themes were identified. The main themes concerned early presentation and identification in the workplace; reasonable adjustments for people with working age dementia; and the provision of information to raise awareness and facilitate informed choice. The evidence suggested that there is a lack of awareness about working age dementia and that this may impact negatively on employees. Guidance for employers offered suggestions for good practice. Conclusions: Guidance for employers is increasingly available although it rarely refers to the evidence base. There is a need for future studies that explore the effectiveness of guidance and training initiatives for employers. Examples of good practice where employees with dementia have been well supported in the workplace and who have been able to leave the workforce with dignity, would be helpful.